GAYA BAHASA DALAM LIRIK LAGU ALBUM DUNIA BATAS KARYA GRUP MUSIK PAYUNG TEDUH - Rajiv Arief Sugesti; Nursal Hakim; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research entitled is Language Style of Song Lyrics of Dunia Batas Album by Payung Teduh Music Group. The problem of this research was “what are the styles of language in song lyric of Dunia Batas album by Payung Teduh music group. It was theoretically and practically useful for the readers. To overcome the problem, the writer used Pradopo and Hasanddin „s theory. This qualitative research was conducted from January 2017 to December 2017. The writer also used qualitative descriptive method. The source of this research was Payung Teduh song lyric which exactly in their second album entitled Dunia Batas. This album had launched fourteen songs in 2012 basically in Compact Disc form. The design of the album was green tosca with a picture of shady tree sketch where in the right down corner was the album title “Dunia Batas” and in the center of the album was “Payung Teduh”. The writer used documentation method for data collecting. Data analysis techniques of this research were descriptive analysis, data presentation, and conclusions. The writer also used triangulation data technique for data validation. Based on the research can be found some results such as collation language style were 4 data, metaphor language style were 2 data, personification language style were 10 data, metonymy language style was 1 data, sinekdoke pars pro toto language style were 4 data, sinekdoke totum pro parte language style were 3 data, allegory language style were 6 data, parable language style was 0 data and fable language style was 0 data. In conclusion, this research describes and proves that song lyric of Dunia Batas album from Payung Teduh music group contain some language styles.Keywords: Language Styles, Lyric, Album